Upper Instrumented Vertebrae (UIV) Tilt Angle Is an Important Postoperative Radiological Parameter That Correlates With Postoperative Neck and Medial Shoulder Imbalance - Chan, Chris Yin Wei; Chiu, Chee Kidd; Ler, Xin Yi; Ng, Yun Hui; Chian, Xue Han; Tan, Pheng Hian; Kwan, Mun Keong (Lippincott, Williams & Wilkins, 2018)
Study Design. Retrospective study. Objective. To investigate the association between postoperative upper instrumented vertebrae (UIV) tilt angle with postoperative medial shoulder and neck imbalance. Summary of Background Data. Studies had found that current recommendations for UIV selection were not predictive of good postoperative shoulder balance. Methods. A total of 98 patients with adolescent idiopathic scoliosis with Lenke 1/2 curves who underwent posterior spinal fusion between 2013 and 2014 with minimum follow-up of 2 years were recruited. Radiological parameters: UIV tilt angle, T1 tilt, cervical axis, and clavicle angle were measured preoperatively, postoperatively, and at final follow-up. Results. Mean age was 16.2±6.2 years. Mean follow-up was 37.9±6.5 months. There were 73.5% Lenke 1 and 26.5% Lenke 2 curves. Significant factors affecting postoperative T1 Tilt were postoperative UIV tilt angle, preoperative T1 tilt, and preoperative UIV tilt angle. Postoperative UIV tilt angle and preoperative cervical axis were significant factors affecting cervical axis at final follow-up. UIV level was not significant independent factor that affected postoperative T1 tilt and cervical axis. There was strong correlation between postoperative UIV tilt angle and T1 tilt for the whole cohort (P<0.001), when UIV was at T2 (P<0.001), T3 (P<0.001), and T4 (P<0.001). Postoperative UIV tilt angle also had significant correlation with cervical axis when UIV was at T2 (P=0.021) and T3 (P=0.009). Conclusion. Postoperative UIV tilt angle was an independent factor, which had significant correlation with postoperative T1 tilt and cervical axis measurement. There was strong correlation between postoperative UIV tilt angle and T1 tilt for the whole cohort, when UIV was at T3 and T4. There was very strong correlation between postoperative UIV tilt angle and T1 tilt when UIV was at T2. There was also moderate and significant correlation between postoperative UIV tilt angle and cervical axis for the whole cohort.